Livestock judging Practice classes I - Creative Educational Video, Inc. (Lubbock, Tex. : CEV Multimedia, 2008)
This program is designed to help students improve their livestock judging skills.
Fakulti Perubatan Veterinar
Gordon Davis, executive producers.
Drew Doughtery, narration.
Keywords: Beef cattle -- Judging -- Study and teaching; Lambs -- Judging -- Study and teaching; Livestock -- Judging -- Study and teaching; Swine -- Judging -- Study and teaching